2018
DOI: 10.2147/jpr.s178103
|View full text |Cite
|
Sign up to set email alerts
|

Organizing palliative care in the rural areas of Iran: are family physician-based approaches suitable?

Abstract: IntroductionThe provision of palliative end-of-life care (P/EOLc) for patients, wherever they live, is an increasingly important service, particularly given the increasing rates of cancer and other life-threatening diseases in Iran. However, unfortunately, those living in the rural areas of Iran are greatly disadvantaged with respect to this type of care. Therefore, the present study explored the feasibility of organizing P/EOLc in the rural areas of Iran.MethodsIn this qualitative study, two focus group (FG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…The important components and findings of final included articles are presented in Table 2 . Results of the study showed that included studies had a focus on different patients/participants including cancer,[ 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ] hemodialysis,[ 45 ] heart failure,[ 46 47 ] chronic disease,[ 48 ] chronic pain,[ 49 ] and with anonymous groups. [ 50 51 52 53 54 55 ] Several provinces/cities were engaged in the studies including Tehran,[ 12 13 14 15 17 20 21 24 25 26 29 30 31 32 33 34 35 37 39 40 41 42 43 48 , 51 , 52 Isfahan,[ 22 27 28 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The important components and findings of final included articles are presented in Table 2 . Results of the study showed that included studies had a focus on different patients/participants including cancer,[ 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ] hemodialysis,[ 45 ] heart failure,[ 46 47 ] chronic disease,[ 48 ] chronic pain,[ 49 ] and with anonymous groups. [ 50 51 52 53 54 55 ] Several provinces/cities were engaged in the studies including Tehran,[ 12 13 14 15 17 20 21 24 25 26 29 30 31 32 33 34 35 37 39 40 41 42 43 48 , 51 , 52 Isfahan,[ 22 27 28 …”
Section: Resultsmentioning
confidence: 99%
“…[ 23 ] Majority of studies had quantitative approach, including interventional,[ 17 18 19 22 23 29 31 33 35 44 47 49 54 ] descriptive,[ 20 39 41 42 50 53 ] and correlational-analytical. [ 37 45 46 51 ] This was then followed by qualitative[ 12 13 14 15 16 21 24 25 26 27 30 32 34 36 40 43 48 52 ] and mixed methods. [ 28 38 55 ] In quantitative interventional PC studies, a range of medical-surgical,[ 17 18 19 23 29 31 33 37 ] educational,[ 44 49 54 ] and psycho-spiritual[ 22 35 ] managements were used as an independent variable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the results of Dy et al, Guirimand et al and Vedel et al, 'availability of the caregivers' and 'serenity' were two important subscales of Quali-Palli-P and the essential components of palliative care quality. [47][48][49] Another subscale was 'providing cure and care information and the patient's involvement in decisions, ' which was emphasised in the studies conducted by Ansari et al, Khoshnazar et al and Jabbari et al [17,50,51] Moreover, Teno et al indicated that patient's participation in carerelated decision-making caused a higher quality of care. [43] Pain management, as well as proper prescribing and applying treatment and care techniques, is other important dimensions of palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…and Jabbari et al . [ 17 , 50 , 51 ] Moreover, Teno et al . indicated that patient’s participation in care-related decision-making caused a higher quality of care.…”
Section: Discussionmentioning
confidence: 99%